Analisis Pengembangan Manajemen Talenta terhadap Kinerja Karyawan pada Badan Kepegawaian Daerah Provinsi Jawa Timur - Reni Fidianingrum; Gendut Sukarno (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
This study aims to determine the effect of recruitment, training, compensation, and competence on the performance of employees of the Regional Personnel Board of East Java province. The population in this study were employees of the Regional Personnel Agency of East Java Province. The sampling method is using probability sampling, namely the probability sampling technique (probability) or simple random sampling. The sample taken amounted to 85 respondents. The data used are primary data, namely questionnaire data from answers to respondents and secondary data, namely supporting data obtained from the Regional Personnel Agency of East Java Province. While the analysis used is Partial Least Square (PLS). Based on the results of research and discussion of research results that have been stated that recruitment, training, and competence have a positive effect on employee performance at the Regional Personnel Agency of East Java Province, while compensation has not affected the performance of employees of the Regional Personnel Agency of East Java Province.